ТЕҢЕЎЛЕРДИҢ ЛИНГВОКУЛЬТУРОЛОГИЯЛЫҚ ӨЗГЕШЕЛИКЛЕРИ (ҚАРАҚАЛПАҚ ХАЛЫҚ ҚОСЫҚЛАРЫ МЫСАЛЫНДА) - Сайманова, А. (FAN va JAMIYAT, 2022)
The article deals with the comparisons used in Karakalpak folk songs and the importance of cultural codes in their creation.